Multi-omics reveals the regulatory effects of Chinese herbal medicine substrates on secondary metabolite biosynthesis in Inonotus glomeratus - Peng, Chengbo; Meng, Meng; Yuan, Xiaolong; Yu, Jiaojun; Wang, Boyi; Zhong, Li; Wang, Yi; Li, Lu; He, Tingwen; Zheng, Yuan (Frontiers in Microbiology, 2025)
IntroductionThe fungal genus Inonotus is renowned for its medicinal properties, including antioxidant and anti-tumor activities, which are largely attributed to its rich repertoire of terpenoid and polyphenolic secondary metabolites. This study aimed to investigate how different Chinese herbal medicine powders used as culture media influence the secondary metabolite profile of Inonotus glomeratus.MethodsThis study employed a multi-omics approach, utilizing Illumina and Nanopore sequencing to assemble a high-quality genome for I. glomeratus. The fungus was cultivated on media containing powders from Polygonum multiflorum, Coix lacryma-jobi, Pisum sativum flour, Salvia miltiorrhiza, Panax ginseng, and Astragalus membranaceus. Subsequent integrated metabolomic and transcriptomic analyses were conducted to profile secondary metabolite production and identify key biosynthetic genes.ResultsExperimental results show that the assembled I. glomeratus genome was 38.68 Mb in size, consisting of 23 scaffolds with a GC content of 47.98%. The genome annotation process identified 67 transcription factors, four polyketide synthases (PKSs), one non-ribosomal peptide synthase, and 11 terpenoid synthases (TPSs). Multi-omics analysis revealed that terpenoid biosynthesis in I. glomeratus was significantly enhanced in DS and RS media. Betulin and betulinic acid exhibited the most dramatic increases in RS medium, reaching 4,658–9,275-fold and 4–503-fold higher concentrations, respectively. The transcriptome results showed that the expression of enzymes such as IgAACT, IgHMGR, IgSQS, IgSES, and IgTPS9 was significantly higher in the RS medium than in the other treatment groups. Integrated metabolomic and transcriptomic analyses suggested that IgPKS1 participates in orsellinic acid biosynthesis. while IgPKS2 is likely involved in naringenin biosynthesis. Additionally, IgTPS9 was associated with betulinic acid biosynthesis, and IgTPS10 contributed to tetracyclic sesquiterpene B-type triterpene formation. Co-expression network analysis and transcription factor binding site prediction indicated that IgMYB3 may regulates IgPKS1 expression, whereas IgHSF1 may simultaneously modulate IgTPS4 and IgTPS6.DiscussionThis study provides novel insights into the regulatory mechanisms governing secondary metabolite production in I. glomeratus. These findings offer a foundation for targeted metabolic engineering and the optimized production of valuable compounds.